Wavelength-switchable and stable-ring-cavity, erbium-doped fiber laser based on Mach–Zehnder interferometer and tunable filter. (2nd March 2018) - He, Wei; Zhu, Lianqing; Dong, Mingli; Lou, Xiaoping; Luo, Fei
Abstract: This paper proposes and tests a ring cavity-based, erbium-doped fiber laser that incorporates a Mach–Zehnder interferometer and tunable filter. A four-m-long erbium-doped fiber was selected as the gain medium. The all-fiber Mach–Zehnder interferometer was composed of two 2 × 2 optical couplers, and the tunable filter was used as wavelength reflector. A lasing threshold of 103 mW was used in the experiment, and the tunable laser with stable single and dual wavelengths was implemented by adjusting the tunable filter. The channel spacing was 0.6 nm within the range 1539.4–1561.6 nm, where the power difference between the lines was less than 0.4 dB. The side-mode suppression ratio was higher than 36 dB and the 3 dB linewidth was 0.02 nm. When a single-wavelength laser was implemented at 1557.4 nm, the power fluctuations were lower than 0.34 dB within 20 min of scan time. When lasers at wavelengths of 1558.6 nm and 1559.2 nm were simultaneously applied, the power shifts were lower than 0.29 dB and 0.43 dB, respectively, at room temperature.